An investigation of wind power potential required in installation of wind energy conversion systems - Akpinar, EK; Akpinar, S (Sage Publications Ltd, 2006)
In the present study, the wind power potential of all the regions (Maden, Agin, Elazig, and Keban) is analysed on the basis of measured hourly time-series wind speed data for the year 2003. The probability density distributions are derived from time-series data and distributional parameters are identified. Two probability density functions are fitted to the measured probability distributions. The wind energy characteristic of all the regions is studied on the basis of the Weibull and the Rayleigh distributions. Using the Weibull probability density function, we estimated the wind energy output and the capacity factor for six different wind turbines between 300 and 2300 kW. It was found that Maden is the best region, among the regions analyzed, for wind energy and wind turbine characteristics.
Keywords: Weibull and Rayleigh distributions; wind energy; wind turbines